Geography Learning Innovation: Google Sites-Based Flipped Classroom Media to Sharpen Critical Thinking Skills: Inovasi Pembelajaran Geografi: Media Flipped Classroom Berbasis Google Sites untuk Mengasah Keterampilan Berpikir Kritis - Faryanti Faryanti; Raimon Efendi; Estuhono (Journal of Vocational Education and Information Technology (JVEIT), 2025)
This study aimed to develop a Google Sites-based learning media integrated with the Flipped Classroom model for Geography learning at SMA Negeri 10 Tebo. The problem addressed in this research was the dominance of conventional lecture-based methods, which limited student engagement and hindered the development of critical thinking skills. The research employed a research and development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed media was validated by experts in content, language, and media, and further tested for practicality and effectiveness through classroom implementation with eleventh-grade students. The findings indicated that the media met the criteria of being highly valid in terms of content accuracy, linguistic clarity, and visual design. The practicality test revealed positive responses from both teachers and students, who acknowledged the media as easy to use, engaging, and supportive of independent learning. The effectiveness test demonstrated a significant improvement in students’ critical thinking skills after utilizing the media. In conclusion, the Google Sites-based learning media integrated with the Flipped Classroom model was proven to be valid, practical, and effective in enhancing Geography learning as well as fostering the development of students’ critical thinking skills